Hard Ticks on Domestic Ruminants and their SeasonalPopulation Dynamics in Yazd Province, Iran - Y Salim abadi; Z Telmadarraiy; H Vatandoost; S Chinikar; MA Oshaghi; M Moradi; E Mirabzadeh Ardakan; S Hekmat; A Nasiri (Tehran University of Medical Sciences, 2010)
Background: Ticks are the main vectors for transmission of different pathogens to human and animals. This survey was performed to find out distribution of ticks, which infested the domestic ruminants in Yazd Province, central Iran during year 2008-2009. Methods: A total number of 30 villages from both mountainous (20%) and plateau (80%) regions of the province were selected randomly. Ticks were colleted from the body of infested animals and transported to the laboratory of Medical Entomology, School of Public Health, Tehran University of Medical Sciences and then were identified to space level using valid identification key. Results: A total of 583 hard ticks were collected. The ticks were classified into three genera and 7 species including:  Hyalomma dromedarii (55.92%), Hy. marginatum (13.20%), Hy. anatolicum (9.78%), Hy. detritum (4.98%),  Hy. asiaticum (3.94%), Rhipicephalus sanguineus (11.84%), and Dermacentor marginatus (0.34%). The highest seasonal activities occurred in summer. The prevalence of the Ixodidae ticks was more evident in plateaus area in Yazd Province. Among the hosts including: cow, goat, sheep and camel, the ticks that collected from camel was more prevalent. The ratio of male was more than female ticks. Hyalomma. dromedarii was the predominant tick species and accounted for 55.92% of the ticks. Conclusion: Some of the collected ticks may play an important role for transmission of vector borne disease to human; therefore, the results of this study will provide a clue for vectors of tick-borne diseases in the region for local authorities for implementation of disease control.